2017
DOI: 10.1145/3072959.3073635
|View full text |Cite
|
Sign up to set email alerts
|

Field-aligned online surface reconstruction

Abstract: Today's 3D scanning pipelines can be classified into two overarching categories: ofine, high accuracy methods that rely on global optimization to reconstruct complex scenes with hundreds of millions of samples, and online methods that produce real-time but low-quality output, usually from structure-from-motion or depth sensors. The method proposed in this paper is the first to combine the benefits of both approaches, supporting online reconstruction of scenes with hundreds of millions of samples from high-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Our approach is quite invariant to these artifacts, as it is able to cope with noise and can either ignore or incorporate varying sample densities. Impressing developments in quad-mesh reconstructions such as Instant Field Aligned Meshes (IFAM) [23] or Online Surface Reconstruction (OSR) [34] produce nice feature-aligned mesh structures, but often struggle with low or varying sample density as demonstrated in comparison with our results. Most recently, learning-based approaches also joined the reconstruction game [32,33] but often require specifically trained models on an explicit object class.…”
Section: Related Workmentioning
confidence: 56%
“…Our approach is quite invariant to these artifacts, as it is able to cope with noise and can either ignore or incorporate varying sample densities. Impressing developments in quad-mesh reconstructions such as Instant Field Aligned Meshes (IFAM) [23] or Online Surface Reconstruction (OSR) [34] produce nice feature-aligned mesh structures, but often struggle with low or varying sample density as demonstrated in comparison with our results. Most recently, learning-based approaches also joined the reconstruction game [32,33] but often require specifically trained models on an explicit object class.…”
Section: Related Workmentioning
confidence: 56%
“…Extensive experiments revealed that very good denoising results cannot be achieved using the following filters: MB [22], PSSRVTK [23], PSRVTK [24], BSR [25], RTM [26], ISR [27], FAOSR [28]. The main reason is incorrect mesh after surface reconstruction, therefore, we do not use these algorithms for our next experiments and comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of the proposed algorithm is compared in terms of the accuracy of 3D object reconstruction and speed with that of the following surface reconstruction algorithms: the marching cubes (MB) [22], the point set surface reconstruction for VTK (PSSRVTK) [23], the Poisson surface reconstruction algorithm in the VTK framework (PSRVTK) [24], the implicit hierarchical B-Splines surface reconstruction based on octree distance field (BSR) [25], the reconstruction of a triangle mesh from a set of oriented 3D points by solving a Poisson system (RTM) [26], the interactive surface reconstruction software with curve-driven controls (ISR) [27], the field-aligned online surface reconstruction (FAOSR) [28], the Ball-pivoting algorithm for surface reconstruction (BPSR) [29], the Poisson surface reconstruction (PSR) [30], the Power Crust algorithm (PC) [31].…”
Section: Introductionmentioning
confidence: 99%
“…Quad re-meshing [62] and retopology provide two alternative systems to get these couples of orthogonal directions while guaranteeing their consistency with local orientation, since they are associated with principal curvature directions and sharp features. Over the last years, quad-dominant meshes gained increasing popularity also in the realitybased modelling field [63,64], for their ability to generate shapes derived from non-contact capture processes more suitable for the computational processes. The quad-dominant meshes can be easily converted into models with different LoD, allowing better rendering of elements under morphing and easier parameterization [65] and enhanced lighting simulations, since the final re-meshed surface has cells aligned with a pair of directions.…”
Section: Mesh Processingmentioning
confidence: 99%